Public policy in a health jurisdiction of Sinaloa, Mexico (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2012)
This research examines public policy in health agencies to develop strategies to know what health jurisdictions in the state of Sinaloa, Mexico. It develops in the theoretical posed David Arellano (2004) about the public organization and its strategy, strategy models put forward by Michael Rubin (1988), Paul Nutt and Robert Backoff (1995) and public policy perspective Eugene Bardach (1998) and Luis Aguilar (2000). The sample was composed of staff of the Sanitary District 2, which covers two municipalities of Sinaloa. There operate 32 health centers. The criteria for selection of interviewees was associated with his role in the ability to decide strategies, which were fourteen. We used the open interview, observation and analysis of text. The number of respondents was considered sufficient, by virtue of their knowledge in the management of general jurisdiction and because the information was provided by the actors directly involved in strategy. It is established that the quality of the information is relevant and necessary interviewed to obtain empirical data, thanks to its strategic position within and outside the organization. It was determined that the strategies are characterized by turbulent and uncertain context, identifying needs them and how difficult it is to obtain resources to meet them, because of that allocation will depend on higher units.
Keywords: public organization; strategy; public policy